Financial Literacy, Digital Literacy and Financing Preferences Role to Micro and Small Enterprises’ Performance - Pepie Diptyana; Nur'aini Rokhmania; Erida Herlina (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This research aims to examine financial literacy, digital literacy and financing preferences influences toward micro and small enterprises (MSEs) performance Design/methodology/approach: This research used quantitative method and SmartPLS were employed to test the hypotheses Findings: financial literacy and digital literacy has significant positive influence to MSEs performance. External financing has negatively significant influence toward performance. Financial literacy is positively significant to internal financing. Research limitations/implications: Due to limitations of response rate, this research model for external financing preferences results limited adjusted r-square. We suggest that next research can expand the samples, and variables. Practical implications: This research implies that MSEs need literacy supports to get reliable information about market access, analyzing financial performance and budget, government policies which affect their financial condition, from universities and governments as policy-maker. Originality/value: There were limited studies which examining MSEs performance for surviving in crisis period. This research provides data about financial literacy, digital literacy and financing preferences to enhance MSEs performance. Paper type: Research paper